Enterprise logic vs product logic: the development of GE's computer product line. Issue 3 (3rd April 2017) - Gandy, Anthony; Edwards, Roy
Abstract: The following article focuses on corporate strategies at General Electric (GE) and how corporate-level interventions impacted the market performance of the firm's general purpose commercial mainframe product set in the period 1960–1968. We show that in periods of both divisional independent planning and corporate-level planning strategic governance, central decisions interfered in the execution of GE's product strategy. GE's institutional 'enterprise logic' negatively impacted the 'product logic' of its computer product line leading to a weakened position in the market for these systems.